1999
DOI: 10.1046/j.1365-201x.1999.00573.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of biochemical methods for single muscle fibre analysis

Abstract: The neural and muscular changes during fatigue produced in repeated submaximal static contractions of knee extensors were measured. Three groups of differently adapted male subjects (power-trained, endurance-trained and untrained, 15 in each) performed the exercise that consisted of 10 trials of submaximal static contractions at the level of 40% of maximal voluntary contraction (MVC) force till exhaustion with the inter-trial rest intervals of 1 min. MVC force, reaction time and patellar reflex time components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
2
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 173 publications
(197 reference statements)
4
73
2
4
Order By: Relevance
“…The MyHC isoform composition of the different palate and control muscle fibres was in general closely correlated with their enzyme-histochemical profile and in agreement with previous observations on MyHC composition in human limb (for reviews see Staron, 1997 ;Pette et al 1999) and facial muscles (Sta/ l et al 1994). Type I fibres contained exclusively slow MyHC and type IIC and IM fibres various proportions of slow MyHC and fast A MyHC.…”
Section: Myosin Heavy Chain Compositionsupporting
confidence: 77%
See 2 more Smart Citations
“…The MyHC isoform composition of the different palate and control muscle fibres was in general closely correlated with their enzyme-histochemical profile and in agreement with previous observations on MyHC composition in human limb (for reviews see Staron, 1997 ;Pette et al 1999) and facial muscles (Sta/ l et al 1994). Type I fibres contained exclusively slow MyHC and type IIC and IM fibres various proportions of slow MyHC and fast A MyHC.…”
Section: Myosin Heavy Chain Compositionsupporting
confidence: 77%
“…Slow MyHC is present in type I fibres and is coexpressed with fast MyHC in type IIC fibres. Fast A MyHC is mainly present in type IIA fibres and fast X MyHC, and not fast B MyHC, is expressed in type IIB fibres (for reviews see Staron, 1997 ;Pette et al 1999). Whether a fast B MyHC is expressed in human muscles is still unclear (Weiss et al 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Type IIX fibers are histochemically very similar to Type IIB fibers and MHC IIx has been shown to be expressed in fibers histochemically identified as Type IIB, but both types differ in their contractile properties (Pette et al, 1999;Smerdu et al, 2009). In contrast to small mammals, results on larger species have shown that only MHC IIa and IIx were expressed but not MHC IIb (e.g., cat: Talmadge et al, 1996;dog: Snow et al, 1982;Š trbenc et al, 2004;goat: Argü ello et al, 2001;sheep: Maier et al, 1992;human: Smerdu et al, 1994;Ennion et al, 1995;horse: Rivero et al, 1996;Eizema et al, 2003;cattle: Tanabe et al, 1998;brown bear: Smerdu et al, 2009).…”
Section: Histochemistrymentioning
confidence: 87%
“…Type IIX fibers were shown to range between IIA and IIB fibers in their contractile properties, such as maximum shortening velocity, myosin ATPase activity, or phosphocreatine levels (for review see Pette et al, 1999), but whether their properties resembled more IIA or IIB fibers depended on the species and muscles studied as well as the specific experimental conditions. In the current study, only three fiber types were distinguished out of the continuum of so far identified muscle fiber (sub)types.…”
Section: Methodological Caveatsmentioning
confidence: 99%